Study on the Instability of Two-Phase Flow in the Heat-Absorbing Tube of Trough Solar Collector - Ying Zhang; Peiyao Liu; Peisheng Li; Yue Chen; Yanni Pan (International Journal of Photoenergy)
The Marangoni effect and Rayleigh-Benard effect in the two-phase region of solar trough heat-absorbing tube are simulated by FTM (front tracking method). Considering the Marangoni effect alone, although surface tension gradient and surface tension affect the interface wave, the two effects have different characteristics. The surface tension gradient caused by the temperature gradient is one of the factors that swing the interface. The amplitude attenuation of the interface wave decreases with the increase of the Marangoni number (Ma). In general, the surface tension gradient enhances the convection opposite to the temperature gradient. Under the gravity field, the Rayleigh-Benard effect influences the development of the vortex structure in the flow field, which in turn affects the velocity gradient near the interface to influence the evolution of the interface fluctuation. In a small Rayleigh number (Ra), the buoyancy convection reduces the velocity gradient, thus suppressing the evolution of the interfacial wave. In the range of Ra < 4.0E4, the larger the Ra, the stronger the inhibitory effect. However, when the Ra number is large (Ra > 4.0E4), the situation is just the opposite. The larger the Ra is, the stronger the promoting effect is.